2022
DOI: 10.1021/acsagscitech.1c00148
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Superhydrophobic Sand Mulches Increase Agricultural Productivity and Water-Use Efficiency in Arid Regions

Abstract: Excessive evaporative loss of water from the topsoil in arid-land agriculture is compensated via irrigation, which exploits massive freshwater resources. The cumulative effects of decades of unsustainable freshwater consumption in many arid regions are now threatening food-water security. While plastic mulches can reduce evaporation from the topsoil, their cost and nonbiodegradability limit their utility. In response, we report on superhydrophobic sand (SHS), a bio-inspired enhancement of common sand with a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 73 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…Recent advances have demonstrated that air layers can be trapped in the liquid–solid interfaces of superhydrophobic materials, which can decrease the contact area between superhydrophobic materials and liquid to show excellent water repellency. Because of their special wettability, these materials are promising for self-cleaning, , oil/water separation, , corrosion resistance, ,, biological techniques, and anti-icing. , Among various functional superhydrophobic coatings, luminescent superhydrophobic coatings have generated particular interest and developed rapidly. They have widespread applications in sunlight conversion of agriculture, anticounterfeiting technologies, , bioimaging , and optoelectronic devices. , Xu et al prepared a fluorinated polypyrene/silica hybrid superhydrophobic film, one-step electrochemical polymerization created rough structures, and strong fluorescence . Char and co-workers fabricated a thermoplastic polyurethane film with green fluoresce by introducing nanocrystals and organic dye .…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have demonstrated that air layers can be trapped in the liquid–solid interfaces of superhydrophobic materials, which can decrease the contact area between superhydrophobic materials and liquid to show excellent water repellency. Because of their special wettability, these materials are promising for self-cleaning, , oil/water separation, , corrosion resistance, ,, biological techniques, and anti-icing. , Among various functional superhydrophobic coatings, luminescent superhydrophobic coatings have generated particular interest and developed rapidly. They have widespread applications in sunlight conversion of agriculture, anticounterfeiting technologies, , bioimaging , and optoelectronic devices. , Xu et al prepared a fluorinated polypyrene/silica hybrid superhydrophobic film, one-step electrochemical polymerization created rough structures, and strong fluorescence . Char and co-workers fabricated a thermoplastic polyurethane film with green fluoresce by introducing nanocrystals and organic dye .…”
Section: Introductionmentioning
confidence: 99%
“…As water evaporation is arrested, more water is available in the plant root region, which boosts plant health in arid regions. In fact, our multi-year field trials of SHS on tomatoes (Solanum lycopersicum), wheat (Triticum aestivum), and barley (Hordeum vulgare) under arid land conditions in western Saudi Arabia have revealed significant enhancements in plant growth and yields (Gallo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, surplus nutrients in rivers are transferred to seas, resulting in nearly 500 instances of hazardous algae blooms in China's shore waters between 2006 and 2012, posing a threat to human health and shore ecosystems [62]. For a sustainable future, technologies that improve the efficiency of agriculture irrigation are required to grow more food or biomass with less water [63]. Because of socioeconomic and climate changes, this scenario is predicted to deteriorate in the future [62].…”
Section: Watermentioning
confidence: 99%